Karakteristik Risiko Kesehatan Non Karsinogen Pada Remaja Siswa Akibat Pajanan Inhalasi Debu Particulate Matter - Ony Rosalia; Bambang Wispriyono; Haryoto Kusnoputranto (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Increase in transport vehicles causes air pollution. Major pollutant of PM2.5 provides an enormous impacton health. Basin condition in Bandung causes the pollutants to be trapped because the pollutant cannot be released.The aim of this research is to analyze the health risks of junior high school students of SMPN 16 Bandungdue to PM2.5 inhalation exposure in the school environment by using Environmental Health Risk Assessment method.PM2.5 concentration assessment was conducted at 10 points with a sample of 66 students’ grade VIII selectedrandomly. The average concentration of PM2.5, which was 29.34 μg/m3 was still below the standard value regulatedby Government Regulation No. 41 of 1999 (65 μg/Nm3). The increased in real-time intake for 3 years and 12years respectively were 7.53x10-5, 1.25x10-4, 5.02x10-4 mg/kg/day. PM2.5 intake was higher in students with lightweight than students with heavy weight. Estimated health risks was expressed as risk quotient (RQ) calculatedfrom the average of PM2.5 exposure intake on students and reference dose (RfC), RQ>1 indicated the risk needed tobe controlled. The results of the analysis with the duration of real-time exposure for 3 years and 12 years showeda safe limit to PM2.5 exposure (RQ<1). Overall grade VIII students are not at risk of PM2.5 inhalation exposure inschool environments.